Opportunities And Challenges For Management Implementation Performance Based On Balance Scorecard - Suryana, Suryana; Tejawiani, Ida; Inayatullah, Qurat-ul-Ain; Tutty Rokhayati, Ade; Nugraha S, Junjun; Ichwan, Rusendra (CV. Inara, 2024)
Implementing the Balance Scorecard (BSC) cannot guarantee the success of an organization in achieving its goal, this depends on how strong the determination is to implement BSC in the organization. Studies regarding the opportunities and challenges faced in the process of implementing or implementing BSC in schools are still very limited. The aims of this research are to: 1). Know, describe and analyze opportunities and challenges in implementing BSC at SMK Negeri 4 Tasikmalaya and SMK Negeri 1 Cipaku Ciamis; 2) describe the opportunities and challenges of implementing BSC at SMK Negeri 4 Tasikmalaya and SMK Negeri 1 Cipaku Ciamis. This research uses a qualitative approach with a descriptive analysis study, collecting primary and secondary data. The analysis technique used in this research follows the Mile’s model. The research results show that as non-profit organizations, SMK Negeri 4 Tasikmalaya and SMK Negeri 1 Cipaku Ciamis are trying to implement BSC to measure their performance. The results of this assessment are contained in the Annual Work Plan (RKT) which is displayed in various strategies with the highest scores in the BSC analysis which will be implemented in the coming year period. Conclusions are : 1) The implementation of BSC at SMK Negeri 4 Tasikmalaya and SMK Negeri 1 Cipaku Ciamis has been implemented well. Viewed from a customer perspective, internal processes, growth and learning as well as a financial perspective, Many schools have implemented the BSC concept and supported BSC-based performance development. 2) chool has challenges in its implementation, especially in terms of collaboration with Dudi. Schools rarely carry out market research to meet industry needs, there is still a lack of commitment from school management in terms of consistent implementation of BSC. Schools also have difficulty measuring and evaluating school progress performance. Schools still experience dependence on BOS and BOPD funds and still lack transparency and accountability in managing school finances.